Teachers‟ Information and Communication Technology Application Skills Influencing English Curriculum Implementation in Schools in Kenya (Journal of Education and Development, 2023)
With English as a universal language and a central player in a globalized digital world, the need for an acceptable level of teacher ICT application skills, competence among teachers of English is necessary. The Government of Kenya (GoK) has put in concerted efforts to propel Kenya towards vision 2030 by investing in ICT integration in curriculum implementation, to equip a professional teacher with ICT skills for quality classroom practices and satisfactory learner performance in national examinations. Despite the efforts by the GoK to equip teachers with ICT skills for good results in English, Kenya National Examinations Council (2022) contends, overall performance in English for the past 5 years falls short of the average mean of 50% and relentless effort from teachers is still required. The purpose of this study was to investigate the influence of teacher level of ICT application skills on implementation of English curriculum in public secondary schools in Kakamega North Sub-County, Kenya. The study used descriptive research design. A sample of 44 principals, 88 teachers of English and 345 form three students across the 50 public secondary schools in Kakamega North Sub-County, Kenya, were targeted. A questionnaire, interview schedule, classroom practice observation schedule, and focus group discussion guide were used to collect data. Qualitative data was analyzed thematically whereas quantitative data was presented through tables, percentages and frequencies. Chi-square test was performed to test hypothesis. Response rate was 79.5%. The findings indicated that there were teachers who neither participated in ICT workshops (67.1%) nor attended conferences on choice of teaching and learning materials (47.1%), a gap pointing on teachers. Interviews and FGD results show, teacher level of ICT application skills is crucial if quality results are to be realized. The study found a significant association between teacher level of ICT application skills and implementation of English curriculum in school. The study concluded, teacher level of ICT skills in teaching of English is a major concern.